Exploring the utility of silane cross-linkers for synthesis of superhydrophobic antibacterial fabrics - Agrawal, Neha (2019)
Textiles are omnipresent materials which find various industrial and household applications in our everyday lives. Functionalization of the textiles with additional properties like superhydrophobicity and antibacterial activity can greatly improve their performance, especially in clothing and healthcare sectors. Despite the existing endeavours to incorporate these properties, fabrication of multi-functional fabrics of high durability through a scalable and eco-friendly technique remains a great challenge. The objective of this research involves developing novel routes of synthesis which are simple, inexpensive, eco-friendly, and can enhance the durability of the superhydrophobic antibacterial fabrics. In this thesis, two different fabrication techniques are reported which utilize fluorine-free silane coupling agents as cross-linkers for improving the durability. Metal-oxide nanoparticles have been employed to offer antibacterial activity and nanoscale roughness, essential to achieve superhydrophobicity and antibacterial functionality on the fabric. The role of the silane cross-linkers involves anchoring the nanoparticles to the fabric surface to enhance the robustness of the coating. In the first synthesis technique, a low surface energy polymer, polydimethylsiloxane (PDMS) was deposited on cotton fabrics. Subsequently, copper oxide (CuO) nanoparticles were deposited on the PDMS coated fabrics with the aid of a silane cross-linker. Three silane cross-linkers, viz., Aminoethylaminopropyltrimethoxysilane (AEAPTMS), Aminopropyltriethoxysilane (APTES), and Methacryloyloxypropyltrimethoxysilane (MPTMS), were explored for their applicability. The as-prepared fabrics displayed high superhydrophobicity and antibacterial performance with water contact angle (WCA) > 153°, water shedding angle (WSA) < 5°, and up to 99% antibacterial efficiency. It was found that 8 g/m2 nanoparticle loading on the fabric surface was optimal in achieving maximum overall performance. The only observed limitation of this technique was the dark colour of the fabrics due to the agglomeration of the black CuO nanoparticles. To overcome this drawback of the first synthesis technique, white zinc oxide (ZnO) nanoparticles were explored for their usage in the second technique. Here, ZnO Abstract ii nanoparticles were deposited on the surface of the cotton fabrics using APTES silane cross-linker followed by modification with Hexadecyltrimethoxysilane (HDTMS), a low surface energy silane. The as-prepared fabrics with an optimized nanoparticle loading of 20 g/m2 displayed high superhydrophobicity with WCA of 153.5° and WSA of 2.4° and up to 98% antibacterial efficiency. Additionally, the ZnO-treated fabrics displayed high UV blocking ability, more than 200 times of pristine cotton fabric. The fabrics synthesised through both the fabrication routes displayed superior durability against abrasion, ultrasonic washing and harsh chemical solutions. Moreover, the air permeability and flexibility of the fabric was not much compromised after the coatings. The above-reported techniques are simple, cost-effective and demonstrate the ability to improve the durability of the synthesized coatings on the cotton fabrics. Both synthesis routes hold tremendous potential for large-scale production of multi-functional fabrics, especially for clothing and healthcare applications.